Police reform as institutional change: Symbols and dilemmas - Terpstra, Jan (International journal of law, crime and justice, 2020)
Many police forces in Western and Northern Europe have been confronted with reform, aimed at drastic changes of their structure, organization, and governance. In this paper these police reforms are understood, not as instrumental, rational processes, but as processes of institutional change. The developments of the Dutch police reform since the late 1980s and especially the Dutch police reform of 2013 are used to show the relevance of the institutional approach. After a sketch of the main outlines of institutional theory and some of the debates that were raised by this approach, the paper concentrates on two critical aspects of institutional theory for understanding processes of police reform: reform symbols and institutional dilemmas. This analysis shows that the symbolic level is fundamental for understanding police reform. Symbols are used both to present and promote the reform, and as counter-symbols to resist it. The result is a complex interplay at the symbolic level. This paper also shows that institutional dilemmas are main drivers of police reform. But on the other hand, the police reforms did not alter these institutional dilemmas fundamentally, an example of the fact that police reform results in both change and continuity. The paper concludes with the suggestion that this institutional approach, with much attention paid to the symbolic level and to institutional dilemmas, may also be relevant for the study of innovations in policing and of the use of new technologies in police work.